2013
DOI: 10.1007/s13277-013-1457-9
|View full text |Cite
|
Sign up to set email alerts
|

The association between cytotoxic T lymphocyte-associated antigen-4 and cervical cancer

Abstract: Cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) gene polymorphisms have been associated with many autoimmune diseases and malignancy susceptibility, but the relationship between CTLA-4 and cervical cancer is still controversial. Hence, a meta-analysis of the published studies for the CTLA-4 gene polymorphisms and the risk of cervical cancer was performed to evaluate the association between them. Odds ratios (ORs) and 95% confidence intervals (CIs) for the codominant, dominant, and recessive genetic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In a stratified analysis by ethnicity, a significant association was observed for CTLA-4c.-319*T allele in Asian, but not in Caucasian women. This meta-analysis confirmed the results of the previous studies ( 79 , 80 ). Of note, in study by Pawlak et al ( 73 ) the significant association between CTLA-4c.-319*T allele and G1 grade of tumor was found.…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4supporting
confidence: 91%
“…In a stratified analysis by ethnicity, a significant association was observed for CTLA-4c.-319*T allele in Asian, but not in Caucasian women. This meta-analysis confirmed the results of the previous studies ( 79 , 80 ). Of note, in study by Pawlak et al ( 73 ) the significant association between CTLA-4c.-319*T allele and G1 grade of tumor was found.…”
Section: Cytotoxic T Lymphocyte-associated Antigen-4supporting
confidence: 91%
“…A large number of genetic association studies suggest that CTLA‐4 is an important susceptibility locus for autoimmune diseases and certain types of cancer; however, the mechanism by which polymorphism of CTLA‐4 acts to inhibit cancer remains unclear. Recently, several studies focused on the association of CTLA‐4 single nucleotide polymorphisms (SNPs) with susceptibility to various types of cancer, such as gastric cancer, cervical cancer, colorectal cancer and lung cancer . Also, a few case‐control studies focused on the association of CTLA‐4 SNPs with susceptibility to HCC .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several studies focused on the association of CTLA-4 single nucleotide polymorphisms (SNPs) with susceptibility to various types of cancer, such as gastric cancer, cervical cancer, colorectal cancer and lung cancer. [7][8][9][10] Also, a few case-control studies focused on the association of CTLA-4 SNPs with susceptibility to HCC. 11,12 However, due to the small sample size and the limited amount of data, the relationship between CTLA-4 SNPs and risk of HCC was not fully understood.…”
mentioning
confidence: 99%
“…The search for high penetrance genetic mutations associated with cervical cancer has proven difficult and has been unsuccessful. Given the fact that single nucleotide polymorphisms (SNPs) represent the most common form of genetic variation, many researchers have shifted their attention to investigate the presence of an association between SNPs in numerous carcinogenic/anti-carcinogenic pathways and susceptibility to cervical cancer in the past decades [9][10][11][12][13]. It has been thought that such low penetrance genetic polymorphisms could confer only modest risk for, or have only moderate protective effect against, cervical cancer if acting individually [52].…”
Section: Emerging Player In Cervical Cancer Susceptibility: Genetic Fmentioning
confidence: 99%
“…In the past decade, it has become more and more evident that host genetic factors and their corresponding protein products could play an equally important role in cervical carcinogenesis by interacting synergistically with HPV oncoproteins [7,8]. In addition, a large number of studies have demonstrated that polymorphic variations within host genetic factors could potentially contribute to the interindividual differences in susceptibility to cervical cancer [9][10][11][12][13]. This observation is particularly true for polymorphisms of host genes involved in the complex carcinogenic and/or anti-carcinogenic pathways.…”
Section: Introductionmentioning
confidence: 99%